In the Name of Elijah Muhammad : Louis Farrakhan and The Nation of Islam - Gardell, Mattias (Book collections on Project MUSE., 1996)
In the Name of Elijah Muhammad tells the story of the Nation of Islam-its rise in northern inner-city ghettos during the Great Depression through its decline following the death of Elijah Muhammad in 1975 to its rejuvenation under the leadership of Louis Farrakhan. Mattias Gardell sets this story within the context of African American social history, the legacy of black nationalism, and the long but hidden Islamic presence in North America. He presents with insight and balance a detailed view of one of the most controversial yet least explored organizations in the United States-and.